Impact of JPY LIBOR Rate Changes on Regulations and Development of Alternative Benchmarks in Japan - Kubacki, Dominik (Journal of Finance and Financial Law, 2023)
The purpose of the article/hypothesis: The considerations presented in this article aim to focus on the final choice of benchmarks in Japan, which operated the LIBOR rate expressed in Japanese yen. In turn, the main purpose of the article is to try to answer whether the newly selected alternative benchmarks in the Tokyo market meet the characteristics of an ideal rate.Methodology: The paper reviews the literature, studies of regulators and index administrators, presenting the stages of reform, the selection of alternative reference rates and making a comparative analysis with the previously functioning LIBOR rate. Due to the subject of the analysis, basic statistical methods were used.Results of the research: The course of benchmark reform in the Japanese market indicates that the reform has been successfully thought out and implemented, and the rates proposed as alternatives are well able to replace the JPY LIBOR rate. However, it should be noted that in this market it was decided that there are three alternatives to choose from covering both interbank rates and risk-free rates. These rates are referred to as: TONA, TIBOR and TORF. Under these circumstances, market participants must consider the optimal choice of comparative options depending on their financial products, the nature of the transactions they are dealing with and their own individual business needs. However, judging whether they are better than the LIBOR rate, the answer is positive because they are based on acts.